Editorial statement: The first year of the European Journal of Government and Economics - Diego Varela; Giacomo Benedetto; Jose Manuel Sanchez-Santos (European Journal of Government and Economics (EJGE), 2012)
In this editorial statement we present a balance of the first year of life of the European Journal of Government and Economics. We discuss the main developments that concern the journal's indexation by academic databases. We also comment on the approval of a code of publication ethics and malpractice. Finally, we emphasise the dangers of excessive technical sophistication and the need to keep an integrated approach between the fields of political science and economics, according to the spirit of the journal.
Keywords: 330; academic journal; economics; indexing; open access; political science